Investigation of inventory record accuracy in product-service system - Rinei, Arifin; Siti Zubaidah, Ismail (Penerbit UMP, 2019)
In this paper we examine Product-Service System (PSS) in manufacturing industries application to inventory control in Malaysian Elaeis Guineensis or known as palm oil industries. We are particularly interested in the record of inventory accuracy for palm oil tree, fresh fruit bunch (FFB) and palm oil. If the inventory is uncontrolled or not accurate, the production will face problems to meet customers demand. We focus not just on inventory activities themselves, but also the key linkages between production, market, supply chain, and oil production. These linkages are examined using generic model using IDEF0 which consists five charts: A0 chart, A1 chart, A2 chart, A3 chart and A4 chart. This paper has provided useful insights into the actual data collection and the preliminary analysis, as well as the contextual and associated information relating to inventory control system. Further research will be to evaluate the generic model development using Technomatix Logistic and Material Flow Simulation Software.